Next-Generation Sequencing of DDX41 in Myeloid Neoplasms Leads to Increased Detection of Germline Alterations - Bannon, Sarah A.; Routbort, Mark J.; Montalban-Bravo, Guillermo; Mehta, Rohtesh S.; Jelloul, Fatima Zahra; Takahashi, Koichi; Daver, Naval; Oran, Betul; Pemmaraju, Naveen; Borthakur, Gautam; Naqvi, Kiran; Issa, Ghayas; et al. (Frontiers in Oncology, 2021)
Previously considered rare, inherited hematologic malignancies are increasingly identified. Germline mutations in the RNA helicase DDX41 predispose to increased lifetime risks of myeloid neoplasms with disease often occurring later in life which presents challenges for germline recognition. To improve identification of germline DDX41, individuals presenting with > 1 DDX41 alteration on an institutional MDS/AML next-generation sequencing based panel at >40% variant allele frequency were flagged for review and genetic counseling referral. Of 5,801 individuals, 90 (1.5%) had ≥1 DDX41 mutation(s) identified. Thirty-eight (42%) patients with a median age of 66 years were referred for genetic counseling; thirty-one were male (81.5%). Thirty-five (92%) referred patients elected to pursue germline evaluation and in 33/35 (94%) a germline DDX41 variant was confirmed. Twenty-two patients (66%) with germline variants reported antecedent cytopenias, seven (21%) had a prior history of malignancy and twenty-seven (82%) reported a family history of cancer. Predictive genetic testing for healthy family members under consideration as stem cell transplant donors was successfully performed in 11 family members, taking an average of 15 days. Near-heterozygous DDX41 mutations identified on next-generation sequencing, particularly nonsense/frameshift variants or those at recurrent germline “hot spots” are highly suggestive of a germline mutation. Next-generation sequencing screening is a feasible tool to screen unselected myeloid neoplasms for germline DDX41 mutations, enabling timely and appropriate care.